Menguatkan Perjanjian Lisan dengan Asas Itikad Baik: Sebuah Kajian Hukum - Panjaitan, Wijaya Natalia (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: Verbal agreements are often a source of dispute due to the lack of written evidence that can be used as evidence. This is due to the absence of good faith from one of the parties who denies the existence of the agreement, making it difficult for the other party to prove that the legal act was agreed upon and then a dispute occurs between the two.Purposes of the Research: The purpose of this study is to examine the strengthening of verbal agreements with the principle of good faith.Methods of the Research: The research method used is Normative Juridical Research with the type of library research.Results of the Research: The implementation of the principle of good faith must be carried out both in written agreements and even in verbal agreements. Especially in verbal agreements, the main capital that binds is trust. So that if there is no good faith in making an agreement, it is tantamount to denying the trust that is the basis for an agreement.